2012
DOI: 10.1177/0890334412441071
|View full text |Cite
|
Sign up to set email alerts
|

Human Colostrum and Breast Milk Contain High Levels of TNF-Related Apoptosis-Inducing Ligand (TRAIL)

Abstract: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A complex biological liquid containing numerous immunoactive agents might play an important role in the anticancer activity of human breast milk. High levels of human soluble TNF-related apoptosis-inducing ligand were found in human colostrum and breast milk, which is an immunoactive substance that plays a key role in controlling apoptosis and cell proliferation in various organs and tissues (Davanzo et al, 2013). Human alpha-lactalbumin made lethal to tumor cells, which is a substance with anticancer activity in human milk, has been reported (Mossberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A complex biological liquid containing numerous immunoactive agents might play an important role in the anticancer activity of human breast milk. High levels of human soluble TNF-related apoptosis-inducing ligand were found in human colostrum and breast milk, which is an immunoactive substance that plays a key role in controlling apoptosis and cell proliferation in various organs and tissues (Davanzo et al, 2013). Human alpha-lactalbumin made lethal to tumor cells, which is a substance with anticancer activity in human milk, has been reported (Mossberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It may be present either in a trans-membrane form or occur in the cytoplasm as a soluble protein. Extremely high levels of TRAIL have been detected in human colostrum and milk (Davanzo et al, 2012). TRAIL is a pleiotropic cytokine with important functions in regulating immune response and inflammation.…”
Section: Tnf -Related Apoptosis Inducing Ligand (Trail)mentioning
confidence: 99%
“…In case of mammals, maternal milk has paramount preventive and therapeutic benefit against vast variety of diseases, including cancer. Numerous studies in humans testify the immunological potential of human milk (Davanzo et al, 2012;Davis, 1998;Harikrishnan, 2006;Mathur et al, 1993;Newman, 1995;Parodi, 2007;Shamsia, 2009;Singh et al, 2012). The global epidemic of cancer is rising with this disease killing more people across the world than tuberculosis, AIDS, and malaria combined.…”
Section: Introductionmentioning
confidence: 99%
“…Using a human prospective birth cohort of 291 healthy term neonates, Belderbos et al [73] reported that breastfeeding significantly modulated innate immune function (e.g., elevated TLR-7 mediated IL-10 cytokine production) compared with formula feeding. Breast milk is also rich in the immunomodulatory, TNF-related, apoptosis-inducing ligand (TRAIL), which is absent in formula [74,75].…”
Section: Breastfeeding and Microbiome Supportmentioning
confidence: 99%